Teacher's Readiness Level in Implementing Work from Home Policy in Indonesia - David Malchiel Ravanelli; Riezky Purnama Ersani Putri; Zahra Karyna Putri; Lina Miftahul Jannah (Indonesian Association for Public Administration (IAPA), 2020)
During the Covid-19 pandemic, the Indonesian Government has implemented Work from Home policy for government employees, including teachers. The duties and obligations of teachers are unique compared to other government employees who provide more administrative services. The teacher must deliver learning to students, whose ultimate goal is to measure student’s abilities on the curriculum. This paper will describe the readiness of teachers in implementing the Work from Home Policy. This study uses the Readiness for Organizational Change theory with four readiness dimensions, namely appropriateness, management support, change-specific efficacy, and personal valence. This study uses quantitative approach by online survey, through accidental sampling, which is analysed with different tests, Mann-Whitney U Test and Kruskal-Wallis H Test. The results show that all dimensions of readiness are at moderate level, and there are differences in the level of teacher’s readiness when compared by regional and age, and there is no difference in the level of teacher’s readiness when compared by education level.